Capital Regulation and Shadow Finance: A Quantitative Analysis - Lee, Hyunju; Lee, Sunyoung; Paluszynski, Radoslaw (Review of Economic Studies, 2024)
Abstract This article studies the effects of higher bank capital requirements. Using new firm-lender matched credit data from South Korea, we document that Basel III coincided with a 25% decline in credit from regulated banks, and an increase of similar magnitude from non-bank (shadow) lenders. We use our data to estimate the effect of capital requirements on bank credit, and the spillover effect of the reform on non-bank lending. We then build a general equilibrium model with heterogeneous banks and firms that replicates these micro estimates. We find that Basel III can account for most of the observed decrease in regulated bank lending and about three quarters of the increase in shadow lending. The latter is driven exclusively by general equilibrium effects of the reform.